The relations between constipation and characteristics of intestinal morphologies by colonoscopy - Xu, Yuting; Xiao, Qili (Frontiers in Gastroenterology, 2023)
Background Constipation is commonly diagnosed throughout the world, and it is typically associated with various factors. However, data on the characteristics of intestinal morphologies linked with constipation are scarce. We examined the association between the characteristics of different intestinal morphologies and constipation. Patients and methods Between March 2020 and February 2021, we enrolled 510 patients from the Affiliated Zhongshan Hospital of Guangzhou University of Chinese Medicine into two groups: 260 in the constipation group and 250 in the control group. Of these patients, intestinal morphology characteristics obtained via colonoscopy were compared and analyzed. Results There were meaningful differences between the cohorts based on the intestinal morphology characteristics of tortuousness (p < 0.001) and dissociation (p < 0.001). In addition, a significant difference in characteristics was determined for either both intestinal morphologies (p < 0.001) or only tortuousness without any other conditions (p=0.015), but there was no significant difference between the two groups with respect to only dissociation without any other conditions (p = 0.077). A subgroup analysis was performed on statistically significant variables—gender (p < 0.001), age (p = 0.002), and operation time (p < 0.001)—and the results showed that regardless of the subgroup analysis, there was a statistically significant difference in tortuousness between the two groups. In addition, there were significantly differences in dissociation between the groups for elderly men and those with a longer operation time. Conclusion Compared with the general population, people with the intestinal morphologies of dissociation and, in particular, tortuousness seem to experience constipation more frequently.